2006
DOI: 10.1002/ajmg.a.31326
|View full text |Cite
|
Sign up to set email alerts
|

Osteocraniostenosis–hypomineralized skull with gracile long bones and splenic hypoplasia. Four new cases with distinctive chondro‐osseous morphology

Abstract: Osteocraniostenosis is a severe skeletal dysplasia characterized by a hypomineralized skull that has been previously described as kleeblattschädel (cloverleaf skull) and overtubulated long bones. Dysmorphic facial features include a short nose, short philtrum, and a small, inverted V-shaped mouth. Splenic a/hypoplasia is a constant finding. We report four infants (two unrelated and two siblings) with osteocraniostenosis and describe the clinical, radiographic and chondro-osseous morphology findings. The two si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Peres et al 2004 recorded a patient with osteocraniostenosis among four patients reported with splenopancreatic fusion. And most recently Elliott et al 2006 report four further patients, one, Case 2, being the subject also of the present report, bringing the total of reported patients to 19, if one accepts the four discussed by Verloes 1997.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Peres et al 2004 recorded a patient with osteocraniostenosis among four patients reported with splenopancreatic fusion. And most recently Elliott et al 2006 report four further patients, one, Case 2, being the subject also of the present report, bringing the total of reported patients to 19, if one accepts the four discussed by Verloes 1997.…”
Section: Discussionmentioning
confidence: 49%
“…This report presents the findings in a newborn male with agenesis of the parietal bones, gracile long bones, and hypoplasia of the spleen, and reviews cranial‐gracile bone syndromes, the concept of “osteocraniostenosis,” and the topic of Kleeblattschädel, cloverleaf skull. This patient is Case 2 in the recent report by Elliott et al 2006.…”
Section: Introductionmentioning
confidence: 73%
“…Classically the long bones of several syndromic associations such as HSS, osteogenesis imperfecta, Marfan syndrome, Cockayne syndrome, Kenny-Caffey syndrome, and osteo-craniostenosis syndrome are principally characterized of being thin and gracile [6,7]. The cardinal bone changes in our current report were derived from conventional radiographic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several characterizations of osteocraniostenosis are craniofacial abnormalities (temporal bulge, small nose, short philtrum, small mouth, and micrognathia), short fingers with tiny nails, pulmonary and splenic hypoplasia, and hydrops. Radiological abnormalities include hypomineralization of the calvarium with resulting cloverleaf skull (acrocephalic), slender tubular bones, thin ribs and clavicles, and metaphyseal flaring of the tubular bones [Kozlowski and Kan, 1988;Verloes et al, 1994;Costa et al, 1998;Kozlowski et al, 2002;Elliot et al, 2006]. Osteocraniostenosis has recently been reviewed by Elliot et al [2006].…”
mentioning
confidence: 99%
“…Radiological abnormalities include hypomineralization of the calvarium with resulting cloverleaf skull (acrocephalic), slender tubular bones, thin ribs and clavicles, and metaphyseal flaring of the tubular bones [Kozlowski and Kan, 1988;Verloes et al, 1994;Costa et al, 1998;Kozlowski et al, 2002;Elliot et al, 2006]. Osteocraniostenosis has recently been reviewed by Elliot et al [2006]. The clinical as well as radiologic findings in the case presented here focuses on the remainder of the SBD (G).…”
mentioning
confidence: 99%